Respostas
respondido por:
0
3 - 2.(x + 13) = x - 18
3 - 2x - 26 = x - 18
- 26 + 3 - 2x = x - 18
- 23 - 2x = x - 18
- 23 + 18 = x + 2x
- 5 = 3x
3x = - 5
x = - 5/3
Resp.: x = - 5
------
3
3 - 2x - 26 = x - 18
- 26 + 3 - 2x = x - 18
- 23 - 2x = x - 18
- 23 + 18 = x + 2x
- 5 = 3x
3x = - 5
x = - 5/3
Resp.: x = - 5
------
3
Anônimo:
ok!
respondido por:
0
3-2 (x+13)=x-18
3 - 2x - 26 = x - 18
- 23 - 2x = x - 18
- 2x - x = - 18 + 23
- 3x = 5(-1)
3x = - 5
x= - 5/3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás